2022
DOI: 10.3389/fonc.2022.964816
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer properties of Caulerpa racemosa by altering expression of Bcl-2, BAX, cleaved caspase 3 and apoptosis in HeLa cancer cell culture

Abstract: The main cause of cervical cancer is infection with Human Papilloma Virus (HPV). Loss of apoptotic control allows cancer cells to survive longer and allows time for mutation accumulation thereby increasing the ability to invade during tumor development. Treatment options for cervical cancer today are surgery, radiotherapy, and chemotherapy. Toxicity to normal cells, adverse side effects, and drug resistance are the main barriers to the use of chemotherapy. Among marine organisms such as bacteria, fungi, actino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These results indicate that resistomycin triggered the cell apoptosis in PC3 cells by regulating apoptosis-related molecules. In accordance with our results, Caulerpa racemosa extract, a marine seaweed, exerted significant anticancer activity by increasing the expression of Bax and cleaved caspase-3 in HeLa cancer cells [51]. Lin et al [52] reported that actinomycin V triggered apoptosis in non-small-cell lung carcinoma A549 cells by upregulating both the protein and mRNA expression levels of p53, p21, and Bax.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that resistomycin triggered the cell apoptosis in PC3 cells by regulating apoptosis-related molecules. In accordance with our results, Caulerpa racemosa extract, a marine seaweed, exerted significant anticancer activity by increasing the expression of Bax and cleaved caspase-3 in HeLa cancer cells [51]. Lin et al [52] reported that actinomycin V triggered apoptosis in non-small-cell lung carcinoma A549 cells by upregulating both the protein and mRNA expression levels of p53, p21, and Bax.…”
Section: Discussionsupporting
confidence: 90%
“…2 A). Bax, Bcl-2, and cleaved caspase-3 are markers of apoptosis [ 21 ]. Grifolin downregulated Bcl-2 expression, upregulated the protein expression of Bax and cleaved caspase 3 in A549 and H1299 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, there may be further compounds of other types present in the green alga C. racemosa which still need to be identified and analyzed, for example through more advanced molecular approaches. Previous studies also highlight the use of algae in inhibiting the replication of the SARS-CoV-2 [ 21 , 22 ], and compounds or extracts from algae have also been found to be effective against other viruses [ 23 , 24 ]. Following these promising results, some studies under in vitro and in vivo conditions are now needed to further investigate the effectiveness of active compounds from C. racemosa in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%